Assembly of dinuclear copper(II) complexes based on a tridentate pyrazol–pyridine ligand: Crystal structures and magnetic properties. (28th May 2017) - Yang, Feng-Lei; Zhu, Guang-Zhou; Liang, Bei-Bei; Shi, Yan-Hui; Li, Xiu-Ling
Graphical abstract: Three dinuclear Cu(II) complexes: [Cu2 ( μ -L)2 H2 ] (H = Cl −, 1 ; H = NO3 −, 2 ; H = CH3 COO −, 3 ), were synthesized with 2-(5-methyl-1H-pyrazol-3-yl)pyridine (HL). All the complexes afford a di-ligand-bridged Cu2 unit, leaving the residual coordination positions occupied by different anionic coligands. Magnetic investigations reveal that the τ values have a greater effect than the coplanarity of the Cu(NN)2 Cu unit on the antiferromagnetic strengths in this system. Abstract: Three dinuclear copper(II) complexes, [Cu2 ( μ -L)2 H2 ] (H = Cl −, 1 ; H = NO3 −, 2 ; H = CH3 COO −, 3 ), were synthesized using the relevant Cu 2+ salts with the tridentate ligand 2-(5-methyl-1H-pyrazol-3-yl)pyridine (HL) by a diffusion or solvothermal method. These compounds were all characterized by element analyses, IR and X-ray single-crystal diffraction. All the complexes afford a di-ligand-bridged Cu2 unit, in which the two Cu 2+ ions and the two ligands are almost coplanar. Each Cu 2+ ion is chelated by the (N–N)pyridine–pyrazole pocket and doubly bridged by the (N–N)pyrazole groups, leaving the remaining coordination positions occupied by different anionic coligands to balance the charge. Magnetic investigations reveal that the τ values have more effect than the coplanarity of the Cu(NN)2 Cu unit on the antiferromagnetic strength in this system.